Impaired renal function is associated with recurrence after cryoballoon catheter ablation for paroxysmal atrial fibrillation: A potential effect of non-pulmonary vein foci. Issue 1 (January 2017) - Yanagisawa, Satoshi; Inden, Yasuya; Kato, Hiroyuki; Fujii, Aya; Mizutani, Yoshiaki; Ito, Tadahiro; Kamikubo, Yosuke; Kanzaki, Yasunori; Ando, Monami; Hirai, Makoto; Shibata, Rei; Murohara, Toyoaki
Abstract: Background: Atrial fibrillation (AF) and chronic kidney disease (CKD) are closely related. The present study aimed to evaluate the association between estimated glomerular filtration rate (eGFR) and outcomes after cryoballoon catheter ablation for AF. Methods: We included a total of 110 patients (64.0 ± 10.1 years, 64% men) with paroxysmal AF who underwent second-generation cryoballoon catheter ablation in this study. Recurrence and change in renal function after ablation were assessed by stratification of eGFR sub-groups. Results: During a mean follow-up period of 9 months, 20 (18%) patients had AF recurrence after the first catheter ablation procedure. Multivariate Cox regression analysis showed that eGFR [hazard ratio (HR) 0.97, 95% confidence interval (CI) 0.93–0.99, p  = 0.047], non-pulmonary vein (PV) ectopic beats at initial ablation (HR 2.92, 95% CI 1.03–8.27, p  = 0.043), and history of stroke (HR 7.47, 95% CI 2.30–24.2, p  = 0.001) were independent predictors of recurrence after the ablation. Among the CKD groups, recurrence was found in 7% (1/15), 12% (9/73), and 46% (10/22) of the eGFR ≥90 mL/min/1.73 m 2, eGFR 60–89.9 mL/min/1.73 m 2, and eGFR 30–59.9 mL/min/1.73 m 2 groups, respectively ( p  = 0.001). Kaplan–Meier survival curves demonstrated that patients with eGFR 30–59.9 mL/min/1.73 m 2 had significantly worse prognosis than did the other groups (log-rank p  < 0.001). In addition, non-PV ectopic beats at initial ablation were detected in 7% (1/15), 14% (10/73), and 50% (11/22) of the patients among the three CKD groups, respectively ( p  < 0.001). No patients developed contrast-induced nephropathy after the catheter ablation procedure. Conclusions: Low eGFR at baseline was an independent predictor of recurrence after cryoballoon ablation for paroxysmal AF. The presence of non-PV ectopic beats was significantly increased in patients with impaired renal function, which might be associated with a poor outcome.